Dimensional accuracy of additive manufacturing model with different internal structure for investment casting implementation - Ibrahim, Mustaffa (2014)
Additive Manufacturing (AM) technology has evolved in manners that are towards diverse possible application. One of AM application is as a sacrificial pattern for Investment Casting (IC) process. The study is focusing on the ability of a Polylactic Acid (PLA) and VisiJet®acrylic material to produce an IC patterns with good dimensional accuracy for ceramic shell fabrication. The AM part is fabricated with a variety of different processes, different internal structure pattern, and different part builds orientation. The AM fabricated parts were then analyzed using the Coordinate Measuring Machine (CMM) to get the average dimension deviation. The results show that part built with 0º built orientation produced a better result compared to part built with 90º built orientation regardless of its internal structure pattern. Even so, among the different internal structure patterns, part with cross internal patternstructure produce better accuracy compared to the others